Digitalization as a Condition for Developing Agriculture and Ensuring Food Security of the Country - KOPTEVA, Lyudmila; ROMANOVA, Irina (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
Digitalization of agriculture is an important tool for radical transformations in its management. Villages now have the opportunity to shift from individual digital technologies to digital integration and a high degree of automation. The technology of data analysis and processing has become the basis for the development of digital agriculture. The study of intelligent systems for storing and analytical modeling of big data is one of the keys to future rural digitalization. This will help solve the pressing problems of the transition to the digital technologies existing today in the country's agriculture. This requires using technologies such as artificial intelligence, statistical data collection, machine learning, mathematical modeling, etc. They will eventually create agriculture with digital integration and a high degree of automation, which will ultimately solve the country's food security problems.